Factors affecting breeding in captive Carnivora - Schmalz-Peixoto, K; von Schmalz-Peixoto, K. E. (2003)
﻿ Captive carnivores pose a challenge for conservationists and institutions alike, presenting many problems that range from diseases to poor welfare and unsuccessful breeding. Available databases of captive populations are rich sources of information that can help determine which factors can affect breeding success and the real potential of these populations in conservation programmes. Some species, such as tigers Panthera tigris, seem to preserve in captivity the same reproductive parameters seen in wild animals, making captive individuals extremely useful in the research of reproductive biology, that can be applied in evolutionary and physiological studies of the order Carnivora. Specific reproductive characteristics, mainly connected with the altriciality of the young, can make some species more prone to lose young in captivity than others, and these factors must be taken into consideration when developing ex situ conservation programmes. Infant mortality in captivity seems to be primarily caused by inadequate maternal behaviour, which can be connected to biological factors as well as to individual characteristics such as origin and rearing methods. Maternal infanticide, either passive or active, is also affected by biological and ecological characteristics of the species, and there may be an effect of the origin of the females, i.e. if they were wildcaught or captive-born. Housing conditions and individual history affect infant mortality, with females that suffered transfer between institutions exhibiting lower breeding success. Also, institutions with thriving research programmes presented higher infant mortality overall, independently of their latitude or management system, which can indicate an effect of human interference. Further research, both in the wild and in captivity, is needed to fully understand the factors affecting breeding success of captive carnivores.